Sosialisasi Pemilu dan Partisipasi Politik: Evaluasi Pemungutan Suara Ulang DPD RI di Sumatera Barat - Waldi, Syahrul; Yusran, Rahmadani (Journal of Civic Education, 2025)
The low level of political participation in the DPD RI re-election in Padang City indicates a problem with the effectiveness of political socialization. This study aims to analyze the influence of political socialization on voter participation in the 2024 DPD RI re-election. The method used is a quantitative approach with an associative research design. The sample was determined using the Slovin formula from the population of voters who did not exercise their right to vote, and data was collected through questionnaires and secondary documentation from the Election Commission (KPU). Data analysis was conducted using correlation tests and simple linear regression. The correlation test results showed a moderate positive relationship between the effectiveness of socialization and participation (r = 0.401; p < 0.01). The coefficient of determination (R² = 0.161) indicates that 16.1% of low participation can be explained by the variable of political socialization effectiveness. The regression value (B = 0.271) confirms that every one-unit decrease in socialization effectiveness reduces participation by 0.271. The results of the study indicate that political socialization has a significant relationship with community political participation. Limited campaign space, a lack of public communication strategies, and low access to information are the dominant factors influencing voters' decisions not to participate. This study recommends improving adaptive and participatory media-based election socialization strategies to increase community involvement in the future elections.